2019
DOI: 10.4103/err.err_4_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surgical outcomes of obstetric brachial plexus birth injury: clinical and electrophysiological study

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Intraoperative finding showed affection of all root with increased frequency of C5 avulsions and C6 rupture. Also Mohasseb et al (13) study showed that love for all roots, specifically C5-T1, was the pathogenic pattern that was most frequently found intraoperatively. The C5 and C6 roots' affliction was the least prevalent pattern.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Intraoperative finding showed affection of all root with increased frequency of C5 avulsions and C6 rupture. Also Mohasseb et al (13) study showed that love for all roots, specifically C5-T1, was the pathogenic pattern that was most frequently found intraoperatively. The C5 and C6 roots' affliction was the least prevalent pattern.…”
Section: Resultsmentioning
confidence: 96%
“…Al Shishtawy (15) discovered in a study of 24 infants with NBPP only three infants were left-sided and 21 were right-sided, indicating that the right side received more affection. Mohasseb et al (13) discovered additional right-sided affection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation